The Role of Cognitive Linguistics in Corporate Storytelling – A Methodological Perspective - Stefania D'Avanzo (MediAzioni, 2022)
Corporate storytelling has been usually investigated from the perspective of both marketing studies (Brown 2006: 734) and corporate communication (Ford et al. 1995; Boje 2001; Clifton et al. 2020), which have emphasized the role played by narratives in corporate identity claims. This work is a pilot study aimed at providing a different methodological perspective applied to corporate narratives. In particular, theories from cognitive linguistics (Rosch 1978; Lakoff, 1987), previously applied to corporate mission statements (Ran et al.1997), will be explored here in corporate narratives. More specifically, cognitive categories including, among others, positive, negative and neutral positioning along with interaction processes (Glaser et al 1968) will be taken into consideration. Positioning, for instance, implies a value structure, as an organization can be positioned at either the positive or negative end of the continuum or at some neutral midpoint. From a general perspective, an identity claim that represents an organization too positively or too negatively may lack credibility to target audiences. Conversely, an identity claim that defines an organization neutrally may construct an identity that audiences consider more reliable. In brief, examples of storytelling employed by centenarian Italian companies (https://www.assocentenari.it/en/index.php) will be explored in order to analyse the ways these companies represent themselves from a cognitive perspective.